Influence of antihail works on ecology of protected territories - A. M. Malkarova (Юг России: экология, развитие)
The main factors of harmful physical influence on natural environment are considered at realization of active influences on cloudy processes. The results of researches of the contents and accumulation of used reagents in areas of long-term works are resulted. The estimation of level of environment pollution is showed. The conclusions about safety of application of active influence technologies are represented.